2019
DOI: 10.12669/pjms.35.4.537
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgeon-performed ultrasound-guided fine needle aspiration cytology with histopathological diagnosis of thyroid nodules

Abstract: Objective: To assess the Solitary thyroid nodules by surgeon-performed ultrasound-guided FNAC and evaluate with the histopathological findings. Methods: This study includes 100 Consecutive patients of a solitary thyroid nodule which were presented to the Outpatients Department of Surgery during the period of two years from September 2016 to August 2018. Exclusion criteria were patients with extra-thyroid swelling, diffuse goiter and multinodular goiter. All patients with a solitary thyroid nodule underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Furthermore, although the prognosis of papillary thyroid carcinoma is relatively good, there is a lack of long-term follow-up data. [17][18][19][20] More and more studies have revealed the importance of prelaryngeal lymph nodes in the metastasis of papillary thyroid carcinoma. Therefore, there is a need to carry out follow-up studies, in order to determine whether the postoperative recurrence and metastasis of papillary thyroid carcinoma can be reduced after prelaryngeal lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although the prognosis of papillary thyroid carcinoma is relatively good, there is a lack of long-term follow-up data. [17][18][19][20] More and more studies have revealed the importance of prelaryngeal lymph nodes in the metastasis of papillary thyroid carcinoma. Therefore, there is a need to carry out follow-up studies, in order to determine whether the postoperative recurrence and metastasis of papillary thyroid carcinoma can be reduced after prelaryngeal lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Though the results of ultrasonography are promising but still a constant need for an adjunct histopathological evaluation is felt to determine the true nature of the disease. 12,13 The results of our study show that ultrasonography is highly specific in ruling out malignancy in thyroid nodules. Out of the total 25 malignant nodules 20 (80%) were correctly identified by sonography and among the 180 benign nodules on biopsy 167 were correctly identified by sonography with a specificity of 92.77%.…”
Section: Discussionmentioning
confidence: 61%
“…Despite the role of highfrequency color Doppler ultrasound in identifying the nature of lymph node lesions, it cannot provide pathological diagnosis. 5 If pathological examination of lymph nodes is carried out, a lymph node biopsy is required to determine the pathological types of lymph node lesions. Ultrasound-guided puncture biopsy is currently recognized as one of the effective means for the diagnosis of lymph node lesions, boasting various advantages such as simple and easy operation, accurate target, less trauma and less bleeding under the guidance of ultrasound.…”
Section: Introductionmentioning
confidence: 99%